Simulation for whole-body vibration to assess ride comfort of a low–medium speed railway vehicle. (March 2017) - Kumar, Vivek; Rastogi, Vikas; Pathak, PM
Vibration in trains constitutes one aspect of the physical environment that can cause discomfort to passengers. In order to assess the vibration, a variety of techniques have been developed and used. The general approach is to acquire acceleration at the passenger–train interface, and to then process these acceleration signals in order to calculate human comfort. However, the comfort index so calculated is independent of the seat characteristics and human parameters. Thus, a human biodynamic model with dynamic seat characteristics is necessary in order to perform true comfort analysis. The biodynamics of human subjects has been a topic of interest over the years, and a number of mathematical models have been established. However, there are only a few studies incorporating biodynamic models in railway applications. So, the present work proposes to evaluate Sperling's Ride Index for a low–medium speed railway vehicle and further to calculate root mean square acceleration of different body parts, as per the International Organization for Standardization (ISO) 2631 guidelines, through bond graph technique. Car body flexibility is also incorporated using modal expansion of a free–free beam. Physiological effects of the vibrations on the human body were analyzed using the criteria specified in ISO 2631.